Inappropriate prescribing of preventative medication in patients with life-limiting illness: a systematic review. Issue 2 (5th January 2016) - Todd, Adam; Husband, Andy; Andrew, Inga; Pearson, Sallie-Anne; Lindsey, Laura; Holmes, Holly
Abstract : Objectives: To systematically review the literature to examine the methods used to identify inappropriate prescribing of preventative medication in patients with life-limiting illness and to detail the nature of medications prescribed. Methods: A systematic literature search of 4 databases was undertaken (MEDLINE, EMBASE, CINAHL, PsycINFO) from inception to April 2015 to identify peer-reviewed, observational studies assessing inappropriate prescribing of preventative medication in patients with life-limiting illness. Inclusion criteria were: participants had a life-limiting illness; prescribed/dispensed/using preventative medication; medication appropriateness assessed as a specific study aim or outcome. Results: We found 19 studies meeting our eligibility criteria. The methods used to assess medication appropriateness included criteria developed for the elderly such as the Beers Criteria, and Screening Tool of Older Persons' potentially inappropriate Prescriptions (STOPP) criteria, Delphi consensus and expert clinical opinion. Lipid-regulating drugs (12 studies), antihypertensive (11 studies) and antidiabetic medications (9 studies) were the most common classes of inappropriate medication identified. Conclusions: Patients with life-limiting illnesses are prescribed preventative medications considered inappropriate in the context of diminished life expectancy. The way in which preventative medication appropriateness is assessed in patients with life-limiting illness varies considerably—with some methodologies utilising criteria previously developed for elderly populations. Given this lack of standardisation, improving the prescribing in this context requires an approach that is specifically designed and validated for populations with life-limiting illness.